2018
DOI: 10.1186/s11671-018-2812-y
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticle-Based Detection of Low Molecular Weight AGEs from In Vitro Glycated Haemoglobin A0 Samples

Abstract: Protein glycation is a major biochemical event that takes place in the plasma of diabetic patients due to increased sugar levels. Extensive glycation leads to the formation of advanced glycation end products (AGEs) that is well known for having detrimental effects on diabetic patients. In the current work, we have glycated the physiologically important protein Haemoglobin A0 in vitro to study AGE formation and activity by using them as a template for gold nanoparticle (GNPs) synthesis. It was found that the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 75 publications
0
4
0
1
Order By: Relevance
“…Also, in a previous study, we have found that advanced glycation end products (AGEs) produced as a result of glycation provide a good reducing environment required for the synthesis of GNPs. 29 Here, we have performed in vitro glycation of human hemoglobin A0 (Hb) at 37 °C by using fructose as a reducing sugar and synthesized GNPs from glycated Hb (HBF) without the use of any additional reducing agents. Unlike the conventional methods reported for chemical or biological syntheses of GNPs, our method was performed at room temperature (RT) (25 °C).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, in a previous study, we have found that advanced glycation end products (AGEs) produced as a result of glycation provide a good reducing environment required for the synthesis of GNPs. 29 Here, we have performed in vitro glycation of human hemoglobin A0 (Hb) at 37 °C by using fructose as a reducing sugar and synthesized GNPs from glycated Hb (HBF) without the use of any additional reducing agents. Unlike the conventional methods reported for chemical or biological syntheses of GNPs, our method was performed at room temperature (RT) (25 °C).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Glycated proteins are capable of synthesizing stable gold nanostructures in combination with a chemical reducing agent owing to their higher reactivity post glycation. Also, in a previous study, we have found that advanced glycation end products (AGEs) produced as a result of glycation provide a good reducing environment required for the synthesis of GNPs . Here, we have performed in vitro glycation of human hemoglobin A0 (Hb) at 37 °C by using fructose as a reducing sugar and synthesized GNPs from glycated Hb (HBF) without the use of any additional reducing agents.…”
Section: Introductionmentioning
confidence: 99%
“…Nonenzymatic glycosylation is studied to induce significant alterations to the folded structure of proteins during the course of the reaction and formation of AGEs. 38 Figure 1A represents the UV−visible absorption spectra of HBF (Non-enzymatic glycosylated Hb) with respect to the HB control.…”
Section: Resultsmentioning
confidence: 99%
“…The procedure for the in vitro synthesis of C dots reported in some studies ,, is strikingly similar to that of in vitro nonenzymatic glycosylation ,, except for the fact that the synthesis of C dots is generally performed at very high temperatures ,, to enable the rearrangement of carbon-containing functional groups. We report for the first time the spontaneous formation of C dots during in vitro glycosylation of Hemoglobin A0 (Hb) using fructose as a reducing sugar at 37 °C.…”
Section: Introductionmentioning
confidence: 98%
“…A glicose disponível em excesso na corrente sanguínea associa-se a radicais livres formando os produtos finais de glicação avançada (AGES). Os AGES apresentam estrutura heterogênea e seus subprodutos comprometem os processos vitais, leva ao aumento do estresse celular e de processos inflamatórios, gerando complicações a curto e longo prazo (MADHAVAN et al, 2018;MONTEIRO et al, 2016) Nas glândulas salivares a diabetes mellitus está associada a má distribuição das células acinares e modificações nos receptores de glicose, levando a uma baixa produção de saliva (ALJERF;ALHAFFAR, 2017;ZALEWSKA et al, 2015;MONTEIRO et al, 2016). Indivíduos pré-diabéticos e indivíduos obesos e com resistência à insulina também apresentam diminuição dos níveis salivares e maiores taxas de estresse oxidativo (ITTICHAICHAROEN; APAIJAI; TANAJAK, 2018).…”
Section: Introductionunclassified